Strain Rate and Anisotropic Microstructure Dependent Mechanical Behaviors of Silkworm Cocoon Shells - Xu, Jun (PLoS One, 2016)
Silkworm cocoons are multi-layered composite structures comprised of high strength silk fiber and sericin, and their mechanical properties have been naturally selected to protect pupas during metamorphosis from various types of external attacks. The present study attempts to gain a comprehensive understanding of the mechanical properties of cocoon shell materials from wild silkworm species Antheraea pernyi under dynamic loading rates. Five dynamic strain rates from 0.00625 s(-1) to 12.5 s(-1) are tested to show the strain rate sensitivity of the cocoon shell material. In the meantime, the anisotropy of the cocoon shell is considered and the cocoon shell specimens are cut along 0°, 45° and 90° orientation to the short axis of cocoons. Typical mechanical properties including Young’s modulus, yield strength, ultimate strength and ultimate strain are extracted and analyzed from the stress-strain curves. Furthermore, the fracture morphologies of the cocoon shell specimens are observed under scanning electron microscopy to help understand the relationship between the mechanical properties and the microstructures of the cocoon material. A discussion on the dynamic strain rate effect on the mechanical properties of cocoon shell material is followed by fitting our experimental results to two previous models, and the effect could be well explained. We also compare natural and dried cocoon materials for the dynamic strain rate effect and interestingly the dried cocoon shells show better overall mechanical properties. This study provides a different perspective on the mechanical properties of cocoon material as a composite material, and provides some insight for bio-inspired engineering materials.